An Efficient Route to Novel Uracil-Based Drug-Like Molecules - Babkov, Denis A.; Chizhov, Alexander O.; Khandazhinskaya, Anastasia L.; Corona, Angela; Esposito, Francesca; Tramontano, Enzo; Seley-Radtke, Katherine L.; Novikov, Mikhail S. (Synthesis, 2015)
In order to identify new antiretroviral agents, a series of novel uracil derivatives have been synthesized. Optimized conditions for coupling of Weinreb amides with aromatic Grignard reagents allow the convenient preparation of key benzophenone intermediates in high yields and purities. The use of a modified silyl Hilbert–Johnson reaction affords the target compounds under mild conditions.
Keywords: uracil; benzophenone; Weinreb amide; Grignard coupling; bromination